(untitled) (Research, Society and Development, 2021)
The ketogenic diet is characterized by being a high-fat, low-carbohydrate, and moderate-protein diet. Epilepsy is defined as a chronic neurological disorder characterized by recurrent and unprovoked seizures and refractory epilepsy occurs when medications do not control the seizures. The aim of this work is to verify the effectiveness of the classic ketogenic diet in the treatment of refractory epilepsy in children and adolescents. The methodology used is based on a literature review, where data collection was carried out using articles, theses and websites. The results found indicate that the ketogenic diet proves to be a safe and effective alternative. However, there are side effects and limitations related to the resistance and difficulties of guardians that can compromise the effectiveness of the treatment. For the success of the diet, it is important to have the cooperation of family members, monitoring by a multidisciplinary team throughout the treatment, and the role of the nutritionist is of paramount importance.